Rehabilitation and Return-to-Work of Patients Acquiring COVID-19 in the Workplace: A Study Protocol for an Observational Cohort Study - Müller, Katrin; Zwingmann, Katharina; Auerswald, Tina; Berger, Ivo; Thomas, Andreas; Schultz, Anna-Lena; Wilhelm, Eva; Weber, Rainer-Christian; Kolb, Franziska; Wastlhuber, Alois; Meder, Sylvia; Stegbauer, Michael (Frontiers in Rehabilitation Sciences, 2022)
Background: In 2020, the novel coronavirus disease (COVID-19) developed into a worldwide pandemic. The course of COVID-19 is diverse, non-specific, and variable: Affected persons suffer from physical, cognitive, and psychological acute and long-term consequences. The symptoms influence everyday life activities, as well as work ability in the short or long-term. Healthcare professionals are considered particularly vulnerable to COVID-19 compared to the general population. In Germany, COVID-19 is recognized as an occupational disease or a work-related accident under certain conditions. Disease-specific rehabilitation is recommended for patients following acute COVID-19 to recover physical and neuropsychological performance and to improve work ability. Currently, there are limited findings on the short-term or long-term impact of COVID-19 as a recognized occupational disease or work-related accident, as well as on rehabilitation programs and associated influencing factors. Thus, the present research project will investigate these questions. Methods: For this observational cohort study, post-acute patients with COVID-19 as a recognized occupational disease or work-related accident according to the insurance regulations for COVID-19 will be recruited at the BG Hospital for Occupational Disease in Bad Reichenhall, Germany. All participants will complete a comprehensive multimodal and interdisciplinary inpatient rehabilitation program for a duration of at least 3 weeks, beginning after their acute COVID-19 infection and depending on their individual indication and severity of disease. Participants will complete medical, functional, motor, psychological, and cognitive measurements at four time points (at the beginning (T1) and end (T2) of inpatient rehabilitation; 6 (T3) and 12 (T4) months after the beginning of inpatient rehabilitation). Discussion: The present research project will help to assess and describe long-term effects of COVID-19 as a recognized occupational disease or work-related accident on physical and neuropsychological health, as well as on everyday activities and work ability of affected insured persons. In addition, this study will investigate influencing factors on severity and course of COVID-19. Furthermore, we will examine rehabilitation needs, measures, occurring specifics, and the feasibility of the rehabilitation procedure and disease development in the patients. The results of the intended study will further advance common recommendations for targeted and tailored rehabilitation management and participation in inpatient rehabilitation.